Bending rod is unnecessary in single-level posterior internal fixation and fusion in treatment of lumbar degenerative diseases - Xiao Han (BMC, 2021)
Abstract Background Bending rod is a routine in lumbar fusion and fixation surgery, but there is no study investigating whether bending rod in one level is necessary. Methods Patients receiving 1 level lumbar fixation and fusion between May 2018 and September 2020 were included with a minimum 6-month follow-up. The routine of bending rod was omitted during fixation. Preoperative and postoperative radiological parameters were compared. Results There were 67 patients included in the study. Segment lordosis angle increased obviously from 10° (1–39°) to 14° (2–30°) immediately after operation (p = 0.000). T5-T12 increased from 22.97 ± 12.31° to 25.52 ± 11.83° by the 3rd months after surgery (p = 0.011). SS decreased from 35.45 ± 10.47 to 32.19 ± 11.37 in 6-month follow-up (p = 0.038), and PI dropped from 56.97 ± 14.24 to 53.19 ± 12.84 (p = 0.016). ROM of SLA decreased from 4.13 ± 3.14° to 1.93 ± 1.87° at that time point (p = 0.028). Those changes were not seen at 12-month follow-up. No evidence of adjacent vertebral disc degeneration was observed at any time point. Conclusions No sagittal imbalance, dynamic instability or adjacent vertebral degeneration was observed by the 12th month after single-segment posterior lumbar fusion with the use of unbent rods. Bending rod could be omitted in 1-level lumbar fusion to simplify the procedure and reduce operating time.